First record of white-eared kob (kobus kob leucotis) in Omo National Park, Ethiopia (artiodactyla, bovidae) - Asfaw, T; Ewnetu, M; Moges, A; Gebre, A; Gebresenbet, F; Bauer, H (Pensoft Publishers, 2022)
White-eared Kob, Kobus kob leucotis, Lichtenstein & Peters, 1853, is known to occur in the Gambela-Boma landscape in western Ethiopia and South Sudan. They live in herds and are generally found near water, in such places as plains, woodlands, swamps, and flood plains. We deployed 36 camera traps in Omo National Park and one of them took two images of a White-eared Kob. This is the first documentation from Omo National Park and showing that its range extends further to Omo than previously known and, therefore, the entire area (Gambella to Omo) can be considered as a range extension.